2021
DOI: 10.1016/j.healun.2021.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cold or warm ischemia and ex-vivo lung perfusion on the release of damage associated molecular patterns and inflammatory cytokines in experimental lung transplantation

Abstract: Effects of cold or warm ischemia and ex-vivo lung perfusion on the release of damage associated molecular patterns and inflammatory cytokines in experimental lung transplantation,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 46 publications
3
15
0
Order By: Relevance
“…Indeed, we previously reported that EVLP mitigated lung damage produced by WI alone, whereas it slightly enhanced the damage noted at the end of CI preservation. 9 In contrast, EVLP markedly amplified the release of inflammatory cytokines both in WI and CI lungs, consistent with the time required for de novo gene expression on reperfusion. 9 Time-course experiments would therefore be helpful to more precisely assess the evolution of lung injury after ischemia alone and after various durations of EVLP.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…Indeed, we previously reported that EVLP mitigated lung damage produced by WI alone, whereas it slightly enhanced the damage noted at the end of CI preservation. 9 In contrast, EVLP markedly amplified the release of inflammatory cytokines both in WI and CI lungs, consistent with the time required for de novo gene expression on reperfusion. 9 Time-course experiments would therefore be helpful to more precisely assess the evolution of lung injury after ischemia alone and after various durations of EVLP.…”
Section: Discussionmentioning
confidence: 59%
“… 9 In contrast, EVLP markedly amplified the release of inflammatory cytokines both in WI and CI lungs, consistent with the time required for de novo gene expression on reperfusion. 9 Time-course experiments would therefore be helpful to more precisely assess the evolution of lung injury after ischemia alone and after various durations of EVLP. Third, we did not evaluate injury patterns after extended durations of CI (>12 h) or prolonged WI times, as can be observed in uncontrolled DCD.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations